Designing Financial Safety Nets to Fit Country Circumstances - Kane, Edward J. (World Bank, Washington, DC, 2014)
The author explains how differences in the informational and contracting environments of countries affect the optimal design of their financial safety nets and their optimal strategies for managing financial crises. He explains how to design and operate safety nets at minimum cost to taxpayers and well-managed banks in countries whose informational and contracting technologies differ. His basic premise is that optimal regulation is not a one-size-fits-all proposition. A country's safety net should be transparent, deterrent to too much risk-taking, and accountable, but the author shows large differences across countries in the transparency and deterrence banks afford their depositors, highlighting why the design of safety nets must allow for differences in the enforceability of private contracts. The weaker a country's informational, ethical, and corporate governance environment, the more a wholly governmental system of explicit deposit guarantees is apt to undermine bank safety and stability. How a country's safety net evolves depends on the ability of the private and public sectors to value banks, discipline risk-taking, and resolve financial difficulties promptly. And political accountability is essential if the public part of these tasks is to evolve effectively and efficiently. As a rule of thumb, safety-net managers should avoid either subsidizing or taxing bank risk-taking, says the author. Even if analysts could formulate a beneficial tax or subsidy rule, it is unlikely that channeling the effect through a government-run deposit insurance system that fails to account publicly for the size of taxpayers' stake could improve upon more straightforward arrangements.